Chronic Obstructive Pulmonary Disease among non-Smokers - Dr. Madhurmay; Dr Vineet; Dr Raj Kamal; Dr Rajiv; Dr. Aman (NMO Journal)
Since tobacco use has been linked to COPD for more than 50 years, this population has served as the foundation for almost all of our knowledge regarding the clinical, physiological, pathological, and radiological aspects of the disease as well as the rates of lung function loss and the effectiveness of various treatments. We stated in 1990 that 25 to 45% of COPD cases among never smokers. According to the 2017 Global Burden of Disease report, smoking is only responsible for 35% of the burden of COPD worldwide, with the majority of cases occurring in high-income nations. Most of the world's remaining 65% of nonsmokers with COPD live in low- and middle-income nations. Other non-smoking risk factors for COPD include exposure to biomass smoke while cooking in poorly ventilated homes, high ambient air pollution levels, occupational exposures to dust and gases, ambient ozone exposure, poverty, recurrent respiratory tract infections in childhood, poorly controlled chronic persistent asthma, and prior tubercular lung disease. Worldwide, non-tobacco-related risk factors, which vary by geographic region, are to blame for around half of all instances of COPD. Inflammation, oxidative stress, airway remodelling, and accelerated lung ageing are potential factors for the development of COPD in never-smokers. Never-smokers with COPD had less severe chronic respiratory symptoms, little to no emphysema, less airflow limitation, and fewer comorbidities than smokers who acquire COPD; however, exacerbations can still happen often. More research- including epidemiological, translational, clinical, and implementation studies- is required to fill in knowledge gaps and promote viable solutions to lessen the burden of COPD in never-smokers. Clinical history and spirometry can be used to diagnose Chronic Obstructive Pulmonary Disease (COPD), but identifying its risk factors is time-consuming and crucial because doing so can stop the disease's progression. Contrary to popular belief, smoking cigarettes is only one of the numerous risk factors for COPD. We have examined the etiology of nonsmoker COPD through this review in an effort to identify the causative risk factor and reduce the disease's morbidity and mortality.